PERSEPSI MASYARAKAT TERHADAP AKHLAK SESAMA REMAJA PADA MASA NEW NORMAL DI JORONG MUDIAK PALUPUAH, NAGARI KOTO RANTANG, KECAMATAN PALUPUAH, KABUPATEN AGAM - Fitri Yulianti; Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the problems found, some teenagers are often alone with the opposite sex. In addition, there are also some teenagers who often hang out in stalls or quiet places with their peers and do bad things such as saying dirty words and smoking with their peers. Therefore, the author is interested in examining how the public's perception of the morals of fellow teenagers in Jorong Mudiak Palupuah, Kenagarian Koto Rantang, Palupuah District, Agam Regency. This type of research uses survey research with a quantitative approach. The location of the research is in the Jorong Mudiak Community, Palupuah, because most adolescent relationships are not in accordance with what they should be and the author also finds various problems that need to be resolved. With primary data taken from the field and secondary data taken indirectly. Based on the results of the author's research, that the public perception of the morals of fellow teenagers in Jorong Mudiak Palupuah, Kenagarian Koto Rantang, Palupuah District, Agam Regency, the overall public perception of the morals of fellow teenagers is a small portion (5.6%) of respondents saying that teenagers always have morals in their environment. Approximately, some (38.3%) of respondents answered that teenagers often have morals in their daily lives, some (38%) of respondents said that teenagers sometimes have morals in their daily lives, some (15%) of respondents assumed that teenagers rarely have morals in their environment. , and a small proportion (1.5%) of respondents gave answers to teenagers who have no morals in the community. Keywords: Public Perception, Youth Morals